Texts, Scribes and Transmission Manuscript Cultures of the Ismaili Communities and Beyond - Momin, Wafi A. (Bloomsbury Academic, 2022)
The past few decades have seen a burgeoning interest in the manuscript cultures of the Muslim world. The study of manuscripts has brought to light new perspectives on the transmission of texts and larger questions of cultural practices passed down within the learned circles of premodern Muslim societies. The intellectual and literary heritage of Ismaili communities, who form a branch of Shi'i Islam, has until recently been preserved in private and largely inaccessible libraries. This open access volume brings together studies offering insights on different aspects of the manuscript cultures nurtured by Ismaili communities until well after the widespread dissemination of printed books. The range of materials transmitted via these manuscripts in Arabic, Persian and Indic languages also reflects the doctrinal and literary preoccupations of Muslims at large and of other groups from the societies in which Ismailis lived. Hence, the manuscripts bear the imprint of their respective cultural contexts, namely a number of regions from the Near East to Central and South Asia. In addition to engaging with multifaceted problems surrounding the processes of textual transmission, the chapters in this book deal with other connected aspects like codicology, scribal and reading practices, educational and social history, authorship, communal script, religious identity and interactions of ideas across ideological denominations. With contributions from specialists and early-career scholars, the volume will be of interest to those working on textual scholarship, manuscript and literary cultures and Islamic studies. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Islamic Publications Ltd.